The Influence of Political Regulation on Sharia Economic Development in Indonesia: A Qualitative Approach - Nuzhuliya Mega Avifa; Elisa Tri Rahayu; Putri Firda Febrianti; Mashudi (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
Through a qualitative approach, this research examines the impact of political regulation on Indonesia's sharia economic growth. With the largest Muslim population in the world, Indonesia has the potential to become a global sharia economic center. The study highlights the importance of strict regulation, such as Act No. 21 of 2008 concerning Sharia Banking, in creating a system conducive to sharia-based economic growth. Among other things, overlapping regulations, a literate sharia monetary system and damage to infrastructure continue to be significant constraints. Literature analysis shows that halal product development, financial stability and policies are important factors in driving sharia economic growth. In addition, cooperation between government, industry and the general public is needed to resolve disputes and improve the state of the sharia economy. It is hoped that the results of this research will provide recommendations to optimize political regulations in accordance with sharia principles, thereby enabling the Indonesian economy to grow in an inclusive and durable way.